Perancangan Buku Profil Alas Outbound Edukasi Sebagai Media Promosi di Desa Simpang - Royyan Surya Arlanda; Aris Sutejo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The profile book is an important element that summarizes information about the company. This includes various aspects, such as company history, company vision and mission, organizational structure, products or services offered, as well as relevant achievements or projects. Technology that continues to develop makes profile books an effective communication tool. Profile books are designed to provide external parties with a general overview of a company's identity, goals and capabilities. This activity was carried out at the Outbound Base which is located in Ngingas Hamlet, Simpang Village, Prambon District. Alas Outbound Education offers various innovative educational programs. However, to achieve the current vision and mission, an important step in increasing community participation is to expand outreach and outreach activities. Therefore, designing the Alas Outbound profile book is an important step in marketing tourist attractions. This profile book design activity uses problem analysis methods and design analysis methods. This method is useful for determining the topic of the problem that will be studied and discussed. This method is carried out by interviewing Alas Outbound business owners. The design analysis method is useful for analyzing the flow in designing a profile book. This activity can be used to carry out field observations (site surveys) and also interviews with several Alas Outbound employees. An important aim of designing this profile book is to be an effective marketing tool for the public or potential investors to support this educational tourism destination.